The Transcription Factor ATF7 Controls Adipocyte Differentiation and Thermogenic Gene Programming - Liu, Yang (iScience, 2019)
Adipocytes function as major players in the regulation of metabolic homeostasis, and factors contributing to adipocyte differentiation and function are promising targets for combatting obesity and associated metabolic disorders. Activating transcription factor 7 (ATF7), a stress-responsive chromatin regulator, is involved in energy metabolism, but the underlying mechanisms remain unknown. Herein, we showed that ATF7 is required for adipocyte differentiation and interacts with histone dimethyltransferase G9a in adipocytes to repress the expression of interferon-stimulated genes, which in turn suppress adipogenesis. Ablation of ATF7 promotes beige fat biogenesis in inguinal white adipose tissue. ATF7 binds to transcriptional regulatory regions of the gene encoding uncoupling protein 1, silencing it by controlling histone H3K9 dimethylation. Our findings demonstrate that ATF7 is a multifunctional adipocyte protein involved in the epigenetic control of development and function in adipose tissues.